From Environmental Knowledge To Action In Universities: Explaining The Sustainability Knowledge-Action Gap - Assia El Meskani; Amina Tourabi; Larbi Yacoubi (Cakrawala: Jurnal Pendidikan, 2026)
Environmental sustainability has become a central concern for higher education institutions worldwide. However, previous research has shown that high levels of environmental knowledge among university students do not consistently translate into pro-environmental behaviour. This narrative literature review examined the environmental knowledge-action gap in higher education by synthesising interdisciplinary studies from multiple global contexts. The study analysed psychological, educational, and institutional mechanisms influencing the translation of sustainability knowledge into action. The findings indicated that behavioural outcomes were influenced by factors such as self-efficacy, social norms, emotions, and opportunities for participation, while many Education for Sustainable Development initiatives remained predominantly knowledge-oriented and weakly participatory. Institutional governance structures and sustainability strategies also affected the mobilisation of sustainability knowledge. The study proposes a four-layer analytical framework integrating empirical evidence, behavioural mechanisms, educational approaches, and institutional governance to better understand how universities can promote meaningful sustainability action.